Optimum Nutrient Requirement of Elephant Foot Yam (Amorphophallus paeoniifolius (Dennst.) Nicolson) Under Coconut Gardens - P. S., Anju; K., Susan John; S., Bhadraray; Jeena, Mathew; S., Sunitha; S. S., Veena (JOURNAL OF ROOT CROPS, 2020)
Among the tropical tuber crops, elephant foot yam (EFY) (Amorphophallus paeoniifolius (Dennst.) Nicolson) is a highly potential and ideal intercrop for the coconut gardens of Kerala. Being highly efficient biologically with good yield potential to the tune of 30-100 t ha-1, it is high nutrient demanding too. Though, there are different nutrient management approaches for the cultivation of this crop, taking into account both crop productivity as well as soil health, balanced nutrition based on soil nutrient status and crop requirement deserves special mention. In this regard, customization of nutrients specific to regions and crops can be considered as one of the key approaches. In the protocol for arriving at the grades of the customized fertilizer formulations, one component is evolving the actual optimum of all nutrients of a particular soil by conducting nutrient omission experiments for major nutrients and nutrient level experiments for secondary and micronutrients. Such experiments were conducted for elephant foot yam under intercropping in coconut gardens of the major tuber crops growing soils of Kerala viz., laterite (AEU 9) and sandy plains (AEU 3). The theoretical optimum (based on weighted average data of the soil test) was N : P : K : Mg : Zn : B : Dolomite @ 71 : 12.5 : 106.5 : 16 : 5.25 : 1.31 : 1000 (AEU 3) and 78 : 12.5 : 90 : 16 : 5.25 : 1.31 : 1000 kg ha-1 (AEU 9) respectively. The weighted average data of nutrients was 0.95 and 1.50% (organic carbon), 61.97 and 69.27 kg ha-1 (available P), 213.96 and 295.87 kg ha-1 (available K), 113.32 and 600.16 ppm (exchangeable Ca), 37.53 and 114.99 (exchangeable Mg), 5.07 and 21.46 ppm (available S), 3.94 and 5.68 ppm (available Zn), 0.70 and 0.82 ppm (available B), 1.79 and 3.79 ppm (available Cu), 101.20 and 64.66 ppm (available Fe) and 18.82 and 37.65 ppm (available Mn) respectively for AEU 3 and AEU 9. Different sub optimal and super optimal levels of the theoretical optimum of nutrients viz., N,P, K, Mg, Zn, B and Dolomite was kept as treatments for conducting these experiments in the two locations of AEU 9 and one location in AEU 3. Based on the corm yield data from these experiments, the actual optimum derived by conducting the NOP (Nutrient Omission Plot) and NLE (Nutrient Level Experiment) was N: P: K: Mg: Zn: B: Dolomite @ 140: 20: 225: 19.2: 4.2: 1.575: 1500 kg ha-1 for AEU 3 and 160:12.5:180: 19.2:6.3:1.975:1500 kg ha-1 for AEU 9 respectively and these experiments formed the basis for calculating the different nutrient use parameters for arriving at the grades of the customized fertilizer formulations.